Partitioning Apomixis Components to Understand and Utilize Gametophytic Apomixis - Kaushal, Pankaj; Dwivedi, Krishna K.; Radhakrishna, Auji; Srivastava, Manoj K.; Kumar, Vinay; Roy, Ajoy Kumar; Malaviya, Devendra R. (Frontiers in Plant Science, 2019)
Apomixis is a method of reproduction to generate clonal seeds and offers tremendous potential to fix heterozygosity and hybrid vigor. The process of apomictic seed development is complex and comprises three distinct components, viz., apomeiosis (leading to formation of unreduced egg cell), parthenogenesis (development of embryo without fertilization) and functional endosperm development. Recently, in many crops, these three components are reported to be uncoupled leading to their partitioning. This review provides insight into the recent status of our understanding surrounding partitioning apomixis components in gametophytic apomictic plants and research avenues that it offers to help understand the biology of apomixis. Possible consequences leading to diversity in seed developmental pathways, resources to understand apomixis, inheritance and identification of candidate gene(s) for partitioned components, as well as contribution towards creation of variability are all discussed. The potential of Panicum maximum, an aposporous crop, is also discussed as a model crop to study partitioning principle and effects. Modifications in cytogenetic status, as well as endosperm imprinting effects arising due to partitioning effects, opens up new opportunities to understand and utilize apomixis components, especially towards synthesizing apomixis in crops.